(untitled) (Universal International Scientific Journal, 2026)
This thesis examines the pedagogical and psychological aspects of the formation of information culture in adolescents in a digital educational environment. The work presents the concept of information culture, its role in the development of adolescents, methods of effective use of digital resources, as well as practical recommendations for the development of information culture based on state policy and presidential decrees.